Analisis Perbedaan Rasio Fundamental Sebelum dan Pada Masa Pandemi Covid-19 Perusahaan Sektor Transportasi yang Terdaftar di Bursa Efek Indonesia - Mileni Wahyu Nisa Oktavia; Nibras Anny Khabibah (Jurnal Akuntansi, 2022)
The Covid-19 pandemic has a critical effect on the global economy. There are many impacts felt by companies in Indonesia. The transportation area is one of the maximum affected industrial sectors. This has a look at ambitions to reveal whether or not there are variations in the fundamental ratios than at some stage in the Covid-19 pandemic in transportation organizations indexed at the Indonesia Stock Exchange. This study is quantitative research that uses a comparative approach. The sample used was determined by purposive sampling with a complete pattern of 17 organizations. Using statistics evaluation strategies with side the shapes of the Wilcoxon signed rank test and Paired samples test a look at wherein the statistic is processed with SPSS 20. The effect of this have a look at imply that there are variations in total assets turnover (TATO), current ratio (CR) and there aren’t any variations in debt to equity (DER), return on assets (ROA) and current ratio (CR) than and at some stage in the Covid-19 pandemic for transportation organizations indexed at the Indonesia Stock Exchange for the 2019-2020 period.Keywords: Covid-19 Pandemic, Fundamental Ratios, Different Test